“Ecological Traps” and “Feeding Oases” in Wintering Grounds and Migrations of Young Greater Spotted Eagles - Aleksander L. Mischenko; Olga V. Sukhanova; Aleksander V. Sharikov; Vladimir N. Melnikov; Rinur H. Bekmansurov; Thomas Tennhardt; Christoph Zöckler (Пернатые хищники и их охрана)
Greater Spotted Eagle (Aquila [Clanga] clanga) is one of the most threatened species of eagles in Europe and Western Siberia. The spatial distribution of birds breeding in Russia at wintering grounds and migration stopovers is still not clear enough. Tagging of six fledglings from the Central Federal District and two fledglings from the Volga Federal District in 2019 and 2022 with GPS-GSM trackers and subsequent remote tracking, combined with field work in some areas, made it possible to identify places with the richest and most accessible food (“forage oases”) and critically dangerous situations leading to death (“ecological traps”) during wintering, migrations and summer vagrancies of young birds. A very high mortality rate was revealed during the period of migrations and wintering: only one of the nine birds remained alive by the autumn of 2023. Probably, the high mortality of immature individuals is one of the main reasons for the decline in the number of the Great Spotted Eagle.